Knowledge Sharing Behavior of Management Undergraduates in Sri Lankan Universities. - Gamage, M; Henegedara, P (NSBM Green University, 2018)
Mission of universities is to equip students with the necessary knowledge for their future careers. Universities focus on creating innovative techniques, which help students to learn through knowledge sharing among the students as well as from educators. An important question for universities is how to focus on socio psychological factors that affect students’ knowledge sharing. Knowledge sharing is dependent on individual cognitions, which is one of the complex task forms. Theory of Planned Behavior is an ideal theory to understand why people choose to share knowledge in some contexts not in others. Present study investigates how attitudes, subjective norms, perceived behavioral control and personality of students affect their intention and behavior to share the knowledge.
Keywords: —knowledge sharing; intention; behavior; personality